Silverlicious - Kann, Victoria ([New York, NY] : Harper, 2011)
When Pinkalicious loses her sweet tooth she turns to the Tooth Fairy for help.
"Ages 5-8,"
Keywords: Teeth -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Tooth Fairy -- Fiction; Teeth -- Fiction; Brothers and sisters -- Fiction